The Contested White Lady: A Critique of New Zealand Cultural Heritage Politics - Lindsay Neill; Eveline Duerr; Alexander Trapeznik (Public History Review, 2012)
This article critiques New Zealand’s cultural heritage politics by positing that vernacular items, like an iconic eatery called the White Lady, does not meet the legislative criteria enabling cultural heritage status. If vernacular artefacts, including ‘kiwiana’, are to be integrated within cultural heritage, then changes within legislation, definitions and participant preconceptions are necessary. This study argues that cultural heritage is dominated by artefacts and historic places; that ‘kiwiana’ and other vernacular items of social history, practice and tradition are relegated. Items of ‘kiwiana’ act as touchstones of identity for New Zealanders. Therefore, their omission distorts the view of New Zealand’s cultural heritage. The application of cultural heritage status to the White Lady is important because of its transcendence of time and social change, its aesthetic, and also because of its present-day hospitality offering.